PTU-061 Efficacy and acceptability of a renew anal insert in patients who have undergone restorative proctocolectomy. (8th June 2018) - Segal, Jonathan; Leo, Cosimo; Hodgkinson, Jonathan; Cavazzoni, Emanuel; Vaizey, Carolynne; Bradshaw, Elissa; Faiz, Omar; Hart, Ailsa; Clark, Susan
Abstract : Introduction: Restorative proctocolectomy (RPC) has gained acceptance in the surgical management of medically refractive ulcerative colitis and cancer prevention in familial adenomatous polyposis (FAP). Incontinence following RPC has not been widely researched. In one study at 10 year follow-up, continence to stool and flatus was present in 79.3% of patients, with 74.4% fully continent overnight. Incontinence following RPC can be multifactorial and be related to pouchitis, cuffitis, impaired pouch emptying and pelvic floor and sphincter weakness. Despite attempting to treat the underlying cause, incontinence may still remain a problem and symptomatic control may be necessary. Methods: This was a single centre prospective study exploring the acceptability and efficacy of the Renew anal insert™ in controlling and improving incontinence in patients with a ileoanal pouch. Patients were included if they had undergone RPC for any reason that had self-reported passive incontinence for >2 weeks and were ≥18 years old at time of enrolment. Patients with incontinence were asked to use the Renew™ insert for 14 days. The International Consultation on Incontinence Questionnaire-Bowels (ICIQ-B) was recorded before the trial of the Renew™ insert and at the end of the 14 days. Results: 15 patients were included in the study. There were 10 males and 5 females. The median age of the patients was 57 (range 24–74). All 15 patients had RPC for ulcerative colitis. One patient was lost to follow up. A comparison of the pre and post-intervention scores were made, with the results summarised in table 1. 8/15 patients were satisfied with the device and 6/15 found the device efficacious. Five patients were totally dissatisfied with the device and 6 reported no efficacy. Conclusions: The Renew anal insert™ may be a treatment that can help patients who have undergone restorative proctocolectomy with faecal incontinence. The Renew anal insert™ in the correct selected patients is both acceptable and efficacious and is associated with significant reduction in night time seepage.